Shock wave velocity measurement in the Al2O3 under ultrahigh pressure - 王峰 彭晓世 刘慎业 李永升 蒋小华 丁永坤 (Chinese physics B, 2011)
in indirect-drive experiment, the blank effect caused by X-rays from Hohlraum will show the dark area in time scale of optical streak camera （OSC）. This blank effect, which was a serious problem in indirect-drive shock wave experiments, has been explained by the semiconductor model. The X-rays cause the band to band transition and the probe laser is absorbed by the intraband transition, which leads to a dark region in time scale of the OSC image. In the experiment, the reflectivity of shock wave front was measured to be about 50% at shock wave velocity 32 km/s and was compared to the theoretical calculations with the Drude free electron model. From the experimental data, it is found that the blank effect can be avoided at radiation temperature of 170 eV if the Al layer is thicker than 60μm.